2023
DOI: 10.1111/vde.13223
|View full text |Cite
|
Sign up to set email alerts
|

Environment rather than breed or body site shapes the skin bacterial community of healthy sheep as revealed by metabarcoding

Stéphanie M. Jost,
Laëtitia Cardona,
Emmanuelle Rohrbach
et al.

Abstract: BackgroundThe skin is inhabited by a variety of micro‐organisms, with bacteria representing the predominant taxon of the skin microbiome. In sheep, the skin bacterial community of healthy animals has been addressed in few studies, only with culture‐based methods or sequencing of cloned amplicons.ObjectivesThe objectives of this study were to determine the sheep skin bacterial community composition by using metabarcoding for a detailed characterisation and to determine the effect of body part, breed and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…Skin bacterial isolation from sheep skin showed that the majority of the species belonged to the families Bacillaceae (43.8 %) and Staphylococcaceae (18.8 %). A previous study analyzing the skin bacterial profile of sheep from different breeds, farms and body sites (Jost et al, 2023) (Haarstad et al, 2014). Interestingly, we also found bacterial species such as B. thuringiensis and Solibacillus sp.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Skin bacterial isolation from sheep skin showed that the majority of the species belonged to the families Bacillaceae (43.8 %) and Staphylococcaceae (18.8 %). A previous study analyzing the skin bacterial profile of sheep from different breeds, farms and body sites (Jost et al, 2023) (Haarstad et al, 2014). Interestingly, we also found bacterial species such as B. thuringiensis and Solibacillus sp.…”
Section: Discussionsupporting
confidence: 56%
“…MALDI-TOF mass spectra were acquired on a microflex Biotyper (Bruker Daltonics, Germany) as described (Cuénod et al, 2021) and the species identified with MABRITECCENTRAL, a database for the comparison and identification of bacterial MALDI-TOF MS spectra (www.mabriteccentral.com) (Mabritec AG). Processed spectra are compared against Bacterial species were selected for the behavioural assays based on their 1) harmlessness (biosafety group 1/1+) ensuring a safe future usage as potential skin probiotic, 2) abundance and 3) VIP-scores as determined in our earlier study (Jost et al, 2023). The VIP-score describes the most influential bacteria for the separation between sheep breeds, body parts and origin by PL-SDA (Jost et al, 2023).…”
Section: Bacteria Identification and Selectionmentioning
confidence: 99%
See 3 more Smart Citations